2006
DOI: 10.1016/j.contraception.2005.06.068
|View full text |Cite
|
Sign up to set email alerts
|

The use of an oral contraceptive containing ethinylestradiol and drospirenone in an extended regimen over 126 days

Abstract: Objective: To assess the bleeding profile, acceptance and safety of an extended 126-day regimen of the oral contraceptive Yasmin® [30 µg ethinylestradiol (EE) and 3 mg drospirenone (DRSP)]. Methods: Using daily diaries, 177 women recorded bleeding events throughout the 126-day cycle. At end of treatment, the women completed questionnaires reflecting their satisfaction with the extended regimen. A subset of 30 women underwent endometrial histology sampling after completion of the extended regimen. Results: Of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 19 publications
(37 reference statements)
0
17
0
2
Order By: Relevance
“…Since cyclooxygenase enzymes and prostaglandins are known to play an important role in the development of several conditions such as dysmenorrhoea, endometriosis and menorrhagia, suppression of this enzyme in the endometrium of patients using drospirenone in an extended regimen may explain the advantages of this regimen in controlling menstrual-related symptoms 18 . A positive correlation was also observed between the level of Cox-2 mRNA in the endometrium and the intensity of menorrhagia, further supporting the role for prostaglandins in the regulation of menstrual bleeding 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Since cyclooxygenase enzymes and prostaglandins are known to play an important role in the development of several conditions such as dysmenorrhoea, endometriosis and menorrhagia, suppression of this enzyme in the endometrium of patients using drospirenone in an extended regimen may explain the advantages of this regimen in controlling menstrual-related symptoms 18 . A positive correlation was also observed between the level of Cox-2 mRNA in the endometrium and the intensity of menorrhagia, further supporting the role for prostaglandins in the regulation of menstrual bleeding 7 .…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and seventy seven women recorded bleeding events, completed satisfaction questionnaires, and a subset of 30 had endometrial biopsies. Amenorrhoea was induced in 40%, a somewhat lower rate than that reported for the previously discussed EE/LNG extended regimens, but in 60% there was a shift to less intense bleeding; 68% were satisfied with the extended regimen and safety was comparable to that seen in a conventional regimen 40 . A study from Israel compared the same formulation of EE and DRSP in a 21/7 regimen vs. an 84/7 regimen in 137 women; there was a significant reduction in the amount of bleeding in the extendedcycle regimen at six months 41 .…”
Section: Discussionmentioning
confidence: 74%
“…Of 177 women, 81% completed the extended regimen. This study showed that the continuous use of this formulation over 126 days was safe, efficacious, well accepted by the users and resulted in a considerable reduction of bleeding [15].…”
Section: Extended Cyclementioning
confidence: 88%